Enhancing the cooling system of a residential building using integrated building information modelling with solar absorption system - Al-Qaysi, Ali Abdulqader Mustafa (2022)
Building energy management is concerned with the energy consumption of the building. The used electricity in the residential building has the highest percentage when applying HVAC systems among all other building services installations and other electric appliances. For that, the present work focuses on the cooling load capacity issues and the methods to reduce the amount of electricity used in the building, particularly in air conditioning systems. In order to achieve this target, three main steps were applied; the first step was calculating the cooling load capacity by using the Cooling Load Temperature Difference method (CLTD) method. The second step was to find a sustainable wall material that could reduce the cooling load requirements using Building Information Model (BIM). The sustainable material was a new type of concrete block with a high insulation capability. The final step was to analyse the required energy of the cooling system device by using an applied Engineering Equation Solver (EES) to obtain accurate results. Two types of cooling systems were tested to determine the economic device based on the energy required to operate them under the same conditions. The two cooling systems were the conventional vapour-compression and solar absorption systems. The EES program evaluates the mathematical model and calculations for these systems to investigate the performance coefficient of the selected air-conditioning systems within (May, June, July and August) months in Iraq. This program evaluated the cooling systems by calculating the cost of used power. The results observed that the use of sustainable material reduces the building energy consumption by about 20%, and the solar absorption system is the best device for cooling systems. The solar absorption system provided the best COP in May, which was 0.8048